2017
DOI: 10.1021/acsami.7b09026
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Control of Mesoporosity and Nanoparticles within Co3O4–CuO Electrospun Nanofibers: Quantum Confinement and Visible Light Photocatalysis Performance

Abstract: The one-dimensional (1D) mesoporous and interconnected nanoparticles (NPs) enriched composite CoO-CuO nanofibers (NFs) in the ratio Co:Cu = 1/4 (CoO-CuO NFs) composite have been synthesized by electrospinning and calcination of mixed polymeric template. Not merely the mesoporous composite CoO-CuO NFs but also single mesoporous CoO NFs and CuO NFs have been produced for comparison. The choice of mixed polymer templates such as polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG) for electrospinning is respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 78 publications
(166 reference statements)
1
50
0
Order By: Relevance
“…1A 25 The diffraction peaks at 35.6 and 38.7 are ascribed to the (À111) and (111) diffraction phases of monoclinic CuO (JCPD standard card no.48-1548), respectively. 27 No diffraction peaks of other phases could be observed; this conrmed high purity of the products. Moreover, as illustrated in Fig.…”
Section: Characterization Of the Cuo/cu 2 O Nanocompositesmentioning
confidence: 93%
“…1A 25 The diffraction peaks at 35.6 and 38.7 are ascribed to the (À111) and (111) diffraction phases of monoclinic CuO (JCPD standard card no.48-1548), respectively. 27 No diffraction peaks of other phases could be observed; this conrmed high purity of the products. Moreover, as illustrated in Fig.…”
Section: Characterization Of the Cuo/cu 2 O Nanocompositesmentioning
confidence: 93%
“…In addition to these peaks, two characteristic satellite peaks are positioned at 943.83 and 962.65 eV in the spectrum of pure CuO, indicating that the copper in pure CuO is Cu 2+ [20,21]. [20,21]. The C-1s core-level profiles of CuO-SWCNT-5 composite are displayed in Figure 4d.…”
Section: Curves C To E Inmentioning
confidence: 98%
“…The binding energy difference between these two peaks, as calculated from the spectra, is 20.02 eV, which matches the value reported for Cu 2+ in the literature. In addition to these peaks, two characteristic satellite peaks are positioned at 943.83 and 962.65 eV in the spectrum of pure CuO, indicating that the copper in pure CuO is Cu 2+ [20,21]. [20,21].…”
Section: Curves C To E Inmentioning
confidence: 99%
“…Hence, the flat‐band potentials of Pure‐CuO and C−CuO HSs were calculated to be 0.54 and 0.35 V (vs. Ag/AgCl electrode), corresponding to 0.76 and 0.57 V (vs. NHE), respectively. The valence band potential of Pure‐CuO and C−CuO HSs were therefore calculate to be 0.76 and 0.57 V (vs. NHE), respectively [22] . It could be clearly observed that the VB potentials of C−CuO HSs was negative than that of Pure‐CuO, indicating that the introduction of C atoms could narrow the band gap of CuO via lifting the VB position.…”
Section: Resultsmentioning
confidence: 97%